Virtual Screening of the Antibacterial Compound Paenibacillus polymyxa against Xanthomonas oryzae pv. oryzae - Andre Chandra; Zhafirah Amalia; Lusiana Hidayati; Megifa Putri Adinale; Loekas Soesanto (Jurnal Biologi Tropis, 2026)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo), threatens rice productivity by up to 80%, making it necessary to develop environmentally friendly biopesticides derived from the secondary metabolites of Paenibacillus polymyxa. This study aims to screen potential antibacterial compounds against three key target proteins: Ketol-acid reductoisomerase (ilvC), Protein nucleotidyltransferase (ydiU), and CTP synthase (pyrG). These targets were evaluated in two specific bacterial strains, PXO99A (where ydiU is identified as TAL effector protein PthXo1) and MAFF 311918. The screening was conducted using PyRx-based molecular docking to assess binding affinities and ADMET analysis to evaluate the pharmacokinetic profiles of the candidates. In silico methods include ligand preparation from PubChem, docking, Discovery Studio visualization, and SwissADME and Deep-PK predictions. The results showed that Fusaricidin A had the highest affinity (–7.9 kcal/mol at ydiU PXO99A), Polymyxin B was universally stable due to its amphipathic nature allowing flexible adaptation to all active sites (–6.8 to –7.4 kcal/mol), and Paenibacillin A was the safest (non-mutagenic, biodegradable, low irritation). This study provides a theoretical basis for the development of Paenibacillus polymyxa antibacterial compounds as safe and precise biopesticidal agents in sustainable agricultural systems.